An Overview on Green Titanium Nanoparticles Based on Plants: Synthesis, Potential Applications and Eco-Friendly Approach.: Pharmaceutical Science-Medicinal Chemistry - Dan, Sneha Olive; Khan, S. H. (International Journal of Life Science and Pharma Research, 2022)
Nanotechnology is generating a lot of buzz across the world, because of its fascinating applications in various disciplines. Due to recent breakthroughs in the nanotechnology sector, metal oxide nanoparticles (NPs) have found a number of uses in a variety of industrial, medicinal, and environmental fields. Titanium dioxide nanoparticles (TiO2 NPs) have been widely utilized in everyday life and maybe manufactured using a variety of physical, chemical, and green approaches. Green synthesis is a non-toxic, cost-effective, and environmentally responsible way to make NPs. The green, chemical, physical, and biological production of TiO2 NPs has received a lot of attention, and these NPs may be analysed using high-tech tools. The current study contains extensive information on the comparative synthesis of TiO2 NPs with various properties and their wide range of applications. Because of the decreased usage of precursors, time-effectiveness, and energy efficiency during green synthesis processes, green approaches have been proved to be more efficient than chemical synthesis methods for TiO2 NPs production. The relevance of green manufacturing of TiO2 nanoparticles using plant extract is discussed in this review study. Recent breakthroughs in the manufacture of TiO2 nanoparticles, from plants have shown promise in various scientific and technological domains. The physical features, crystal properties, antibacterial, anticancer, and photo catalytic activity of TiO2 are summarised in this review. The many components of the green synthesis strategy for TiO2 NPs and medicinal applications were discussed. Nanoparticle stability and toxicity, as well as surface engineering strategies for ensuring biocompatibility, are also reviewed. Furthermore, the obstacles and concerns surrounding using green product TiO2 NPs in water and wastewater treatment were explored. Hence, this review article condenses TiO2 NPs physicochemical properties, green synthesis, toxic exposure, biodistribution, and applications.